Gambaran Resiko Ergonomi Menggunakan Metode (NBM) pada Karyawan Kantor PT.PLN (Persero) Surabaya Selatan - Achmad Isya Nyoman; Abdul Hakim Zakkiy Fasya; British Shimahero; Reza Maulana Nur Hidayat (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
In today's use of computers has a very diverse function in human activities, it is found that most office workers complete more than 75% of the duration of their work sitting in front of the computer. Computer users or office workers often experience health problems related to Musculoskeletal Disorder (MSDs) is a health problem that can reduce the function of muscles, tendons, nerves, blood vessels, bones, and ligaments caused by awkward posture, ergonomic risks that often occur in office workers. The research method used is an analytical method. February 2023. PT PLN (Persero) UP3 South Surabaya has six ULP, namely Rungkut ULP, Darmo Permai ULP, Dukuh Kupang ULP, Ngagel ULP, Gedangan ULP. There were 50% of respondents aged >35 years, male gender 55%, working period >10 years 64%, and 68% work duration for 6-8 working hours. The results of the NBM analysis provide information on changes in the distribution of musculoskeletaldisorders (MSDs) complaint rates of office workers are not sick (TS) = 4 5%, somewhat sick (AS) = 43.1%, sick (S) = 10.5%, very sick (SS) = 2.4%. The most dominant type of complaint for S complaint levels both before and after work is "pain in the waist and back". Scoring using the Nordic Body Map (NBM) questionnaire occurs in the upper neck, lower neck, back and waist. Control that can be done to minimize these complaints can be in the form of stretching every 2 hours for 10-15 minutes and regular exercise. In addition, you can also socialize the importance of office ergonomics in the office area using poster media.